Pengaruh Produk Dan Harga Terhadap Minat Beli Ulang Sepeda Motor Honda Scoopy Pada PT Astra Motor Honda Cabang Makassar - Tahir, Bungatang; Sugiarto, Sigit (Insan Cita Bongaya Research Journal, 2023)
This study uses secondary data through the slovin formula method. Based on the results of the slovin formula, the samples used in this study were 92 consumers of PT. Astra Motor Honda Alauddin Makassar Branch. This study aims to examine and analyze the effect of product and price on the intention to repurchase Honda Scoopy motorcycles at PT. Astra Motor Honda Alauddin Makassar Branch, either simultaneously or partially. Based on the results of data analysis and hypothesis testing, this study shows that the results of the F test indicate that Product and Price simultaneously influence Repurchase Intention. The results of the t test also show that partially the Product and Price variables significantly influence Repurchase Intention.